DAMPs/PAMPs induce monocytic TLR activation and tolerance in COVID-19 patients; nucleic acid binding scavengers can counteract such TLR agonists. (April 2022) - Naqvi, Ibtehaj; Giroux, Nicholas; Olson, Lyra; Morrison, Sarah Ahn; Llanga, Telmo; Akinade, Tolu O.; Zhu, Yuefei; Zhong, Yiling; Bose, Shree; Arvai, Stephanie; Abramson, Karen; Chen, Lingye; et al.
Abstract: Millions of COVID-19 patients have succumbed to respiratory and systemic inflammation. Hyperstimulation of toll-like receptor (TLR) signaling is a key driver of immunopathology following infection by viruses. We found that severely ill COVID-19 patients in the Intensive Care Unit (ICU) display hallmarks of such hyper-stimulation with abundant agonists of nucleic acid-sensing TLRs present in their blood and lungs. These nucleic acid-containing Damage and Pathogen Associated Molecular Patterns (DAMPs/PAMPs) can be depleted using nucleic acid-binding microfibers to limit the patient samples' ability to hyperactivate such innate immune receptors. Single-cell RNA-sequencing revealed that CD16 + monocytes from deceased but not recovered ICU patients exhibit a TLR-tolerant phenotype and a deficient anti-viral response after ex vivo TLR stimulation. Plasma proteomics confirmed such myeloid hyperactivation and revealed DAMP/PAMP carrier consumption in deceased patients. Treatment of these COVID-19 patient samples with MnO nanoparticles effectively neutralizes TLR activation by the abundant nucleic acid-containing DAMPs/PAMPs present in their lungs and blood. Finally, MnO nanoscavenger treatment limits the ability of DAMPs/PAMPs to induce TLR tolerance in monocytes. Thus, treatment with microfiber- or nanoparticle-based DAMP/PAMP scavengers may prove useful for limiting SARS-CoV-2 induced hyperinflammation, preventing monocytic TLR tolerance, and improving outcomes in severely ill COVID-19 patients.